On the Question of How Social Rules and Social Norms Exist - Christian Bispinck-Funke (Phenomenology and Mind, 2017)
The objective of this paper is to grasp the mode of being of social rules and norms. I begin by analyzing how mental representations of rules and norms structure social interaction. Then I demonstrate that the actual existence of rules and norms is a multi-dimensional phenomenon that encompasses mental and linguistic realization (linguistically expressed or habituated doxastic attitudes) as well as socially organized bindingness. I conclude that social rules and norms can be described merely by refering to dispositions and notions.